Viral Acute Lower Respiratory Tract Infections (ALRI) in Rural Bangladeshi Children Prior to the COVID‐19 Pandemic - Reller, Megan E.; Mehta, Kayur; McCollum, Eric D.; Ahmed, Salahuddin; Anderson, Jack; Roy, Arunangshu D.; Chowdhury, Nabidul Haque; Saha, Samir; Moulton, Lawrence H.; Santosham, Mathuram; Baqui, Abdullah H. (Influenza and other respiratory viruses, 2024)
ABSTRACT Background Acute lower respiratory tract infections (ALRIs) remain the leading infectious cause of death among children < 5 years, with viruses contributing to a large proportion of cases. Little is known about the epidemiology and etiology of viral ALRI in rural Bangladesh. Methods We enrolled 3‐ to 23‐month‐old children with ALRIs attending a subdistrict hospital outpatient clinic in Sylhet district in Bangladesh. Trained study physicians ascertained the cases and obtained nasopharyngeal swabs to detect 19 respiratory viruses by multiplex PCR using the Luminex Integrated System NxTAG Respiratory pathogen panel. Results Between August 2016 and September 2017, we enrolled 1477 children. Median age was 10 months; 58.1% were male. Forty‐seven percent presented during autumn (mid‐June to mid‐October). About a third had temperature ≥ 101°F, 95.4% had cough in the previous 3 days, 72.0% had fast breathing, and 80.0% had chest indrawing. Alveolar consolidation occurred in 23.9%, and 4.4% were hypoxemic (saturation < 90% on room air). Nineteen percent required hospitalization; 79.1% of them were discharged within 48 h. A respiratory virus was identified in 81.8%, majority (75.8%) with single virus isolation. Rhinoenterovirus was most commonly identified (HRV/HEV, 37.9%), followed by respiratory syncytial virus (RSV, 20.2%) and human metapneumovirus (hMPV, 11.7%). Rhinoenterovirus was detected year‐round; RSV was detected during August–November and hMPV during December–March. Conclusions Respiratory viruses were identified in a majority (82%) of children under 2 years of age presenting with ALRI in rural hospitals of Bangladesh. These findings have implications for future study and potentially for surveillance, antimicrobial stewardship, vaccine program planning, and policy.